2017
DOI: 10.1093/ejcts/ezx179
|View full text |Cite
|
Sign up to set email alerts
|

Surgical ablation for persistent atrial fibrillation in concomitant cardiac surgery: mid-long-term result†

Abstract: Surgical ablation has a high success rate and may improve cardiac function postoperatively. AF/AFL at discharge, preoperative right atrial diameter, hypertension, diabetes and smoking are the major independent predictors for ablation failure. Reintervention in AF/AFL recurrent patients can achieve a favourable clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 19 publications
3
16
1
1
Order By: Relevance
“…Ad et al also demonstrated improved quality of life through SF-12 and AF-specific questionnaire in the elderly cohort > 75 years who had concomitant Cox-Maze IV [18]. Gu et al showed patients who were restored to SR postoperatively had significantly better NYHA status compared to those in AF [29]. They also demonstrated significantly improved LVF and decreased size of LA and RA [29].…”
Section: Discussionmentioning
confidence: 99%
“…Ad et al also demonstrated improved quality of life through SF-12 and AF-specific questionnaire in the elderly cohort > 75 years who had concomitant Cox-Maze IV [18]. Gu et al showed patients who were restored to SR postoperatively had significantly better NYHA status compared to those in AF [29]. They also demonstrated significantly improved LVF and decreased size of LA and RA [29].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiopulmonary bypass was established via aorto-bicaval cannulation. For surgical ablation (SA), the standard Cox-Maze IV procedure was performed using a Medtronic radiofrequency ablation kit (14)(15)(16). The LA appendage was routinely cut and oversewn.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Although not certain, the biatrial lesion set appears to display superiority to isolated LA lesion set in prevention of AF recurrence [78,80]. In addition, modifiable risk factors such as hypertension, diabetes and smoking are implicated in surgical ablation failure [81].…”
Section: Predictors Of Af Recurrence Following Surgical Ablationmentioning
confidence: 99%